2018
DOI: 10.3748/wjg.v24.i26.2893
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal tract capsule endoscopy using a nurse-led protocol: First reported experience

Abstract: AIMTo test the feasibility and performance of a novel upper gastrointestinal (GI) capsule endoscope using a nurse-led protocol.METHODSWe conducted a prospective cohort analysis of patients who declined gastroscopy (oesophagogastroduodenoscopy, OGD) but who consented to upper GI capsule endoscopy. Patients swallowed the upper GI capsule following ingestion of 1 liter of water (containing simethicone). A series of positional changes were used to exploit the effects of water flow and move the upper GI capsule fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…By using simethicone and repetitive position change, the gastric cleanliness in this study was considered good to excellent, which was similar to previous studies [ 20 , 21 ]. Compared to the results of Ching HL et al [ 30 ], our study showed that only 1.95% and 3.91% of patients had insufficient cardia and fundus examinations, respectively. The relevant poor visibility of MCE in the upper stomach was probably due to the mucus and bubbles being retained by the deep mucosal folds of the greater curvature [ 6 , 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 93%
“…By using simethicone and repetitive position change, the gastric cleanliness in this study was considered good to excellent, which was similar to previous studies [ 20 , 21 ]. Compared to the results of Ching HL et al [ 30 ], our study showed that only 1.95% and 3.91% of patients had insufficient cardia and fundus examinations, respectively. The relevant poor visibility of MCE in the upper stomach was probably due to the mucus and bubbles being retained by the deep mucosal folds of the greater curvature [ 6 , 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 93%
“…RCTs demonstrate that antifoaming agents improve the quality of mucosal visualization, 10,14 and meta-analyses have concluded that simethicone has a positive impact on the quality of preparation as it significantly decreases the presence of luminal bubbles/foam. 14,17,18,24,26,3455 The combination of purgatives and antifoaming agents does not increase diagnostic yield; however, it may play a role in improving the quality of small-bowel mucosal visualization.…”
Section: Performance Measures For Sbcementioning
confidence: 99%
“…The average capsule transit time through the esophagus can be as low as about 30 s [59], mandating a fast frame rate to capture highquality images; once it enters the stomach, the uncontrolled capsule movement further complicates image acquisition. Using the Pillcam UGI capsule that captures 35 frames per second, capsule endoscopy has been shown to visualize important clinical landmarks of the esophagus; in addition, feasibility to view the entire stomach was demonstrated with patients positioned at different planes and angles on an examination bed in a nurse-led protocol [59]. Owing to its moderate accuracy (sensitivity 78% and specificity 73% for BE detection in a meta-analysis of nine studies involving 618 patients by Bhardwaj et al), however, it is not recommended for BE screening [7,60].…”
Section: Capsule Endoscopymentioning
confidence: 99%